Analisis Dampak dan Risiko Layanan Peer-to-Peer (P2P) Lending Syariah di Indonesia - Khairul Katsirin; Iswandi Akbar; Nurlaili Akbar; Malfiandri (Cendekia Inovatif Dan Berbudaya, 2026)
The development of information technology and the transformation of the financial system have given rise to innovative digital financing services known as Peer-to-Peer (P2P) Lending. Along with the increasing public demand for financial products that are lawful and compliant with Sharia principles, a variant of this service called Islamic P2P Lending has been developed. This study aims to analyze the impacts and identify the inherent risks associated with the operations of such services in Indonesia. The research employs a literature review method with a descriptive qualitative approach, collecting data from official regulations, industry reports, and national and international scientific journals accessible to the public. The findings reveal that Islamic P2P Lending provides positive impacts, including improved financial inclusion, support for the growth of Micro, Small, and Medium Enterprises (MSMEs), and the availability of alternative halal investment options. Nevertheless, this service also faces various risks, such as default risk, Sharia non-compliance, technological system failures and data security issues, as well as legal and reputational risks. Therefore, strengthened supervision, enhanced financial literacy, and the implementation of risk mitigation strategies in accordance with Sharia principles are necessary to ensure the sound and sustainable development of this service.